Brayton cycle numerical modeling using the RELAP5-3D code, version 4.3.4 (Brazilian Journal of Radiation Sciences (BJRS), 2019)
This work contributes to enable and develop technologies to mount fast microreactors, to generate heat and electric energy, for the purpose to warm and to supply electrically spacecraft equipment and, also, the production of nuclear space propulsion effect. So, for this purpose, the Brayton Cycle demonstrates to be an optimum approach for space nuclear power. The Brayton thermal cycle gas has as characteristic to be a closed cycle, with two adiabatic processes and two isobaric processes. The components performing the cycle's processes are compressor, turbine, heat source, cold source and recuperator. Therefore, the working fluid’s mass flow runs the thermal cycle that converts thermal energy into electrical energy, able to use in spaces and land devices. The objective is numerically to model the Brayton thermal cycle gas on nominal operation with one turbomachine composed for a radial-inflow compressor and turbine of a 40.8 kWe Brayton Rotating Unit (BRU). The Brayton cycle numerical modeling is being performed with the program RELAP5-3D, version 4.3.4. The nominal operation uses as working fluid a mixture 40 g/mole He-Xe with a flow rate of 1.85 kg/s, shaft rotational speed of 45 krpm, compressor and turbine inlet temperature of 400 K and 1149 K, respectively, and compressor exit pressure 0.931 MPa. Then, the aim is to get physical corresponding data to operate each cycle component and the general cycle on this nominal operation.